A negative photoresist composition and its application
By using a negative photoresist composition composed of the first acrylic resin and the second acrylic resin, combined with a photoacid generator and a solvent, the problems of volatile and insufficient mechanical properties of the existing photoresist materials during the process are solved, and efficient and environmentally friendly photoresist material preparation is achieved, with good mechanical properties and elastic recovery rate.
Patent Information
- Application Number
- CN202411874031.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-19
AI Technical Summary
Existing photoresist materials are prone to volatilization during the process, resulting in equipment contamination, and insufficient mechanical properties and elastic recovery rates, making it difficult to meet the process conditions for display panel preparation.
A negative photoresist composition composed of the first acrylic resin and the second acrylic resin is used to combine a photoacid generator and a solvent to prepare a photoresist material with good mechanical properties and elastic recovery rate through polymerization.
The good resolution, residual film rate and elastic recovery rate of the photoresist material are achieved, the equipment pollution caused by small molecules is avoided, and the mechanical properties and adhesion of the material are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoresists and relates to a negative photoresist composition and application thereof. Background Art
[0002] Photoresist compositions are usually composed of polymer resins, photoinitiators, reactive diluents and solvents, and are mainly used to manufacture microelectronic components, such as computer chips and integrated circuits. Since photoresist materials have photochemical sensitivity, they can be used to undergo photochemical reactions to form solidification and crosslinking. According to their development principles, they can be divided into positive photoresists and negative photoresists. The development principle of negative photoresists is that the photoresist layer is exposed to an activating radiation source through a mask, and the activating radiation source causes the photoresist layer to undergo a photoinduced crosslinking reaction. After imaging exposure, the corresponding pattern can be obtained by developing it.
[0003] Traditional spacers (interspacers) are materials of ball spcers, which are dispersed on CF substrates through a spraying process. However, due to the unevenness of the spraying process, the disadvantage of easy agglomeration has been eliminated in the current production line. Photoresist materials can use photolithography methods to directly pass the materials through coating, pre-baking, exposure, post-baking, development, hardening and other steps to obtain spacers with the required thickness and gap arrangement to provide support for the substrate. It also has the advantages of good uniformity, controllable gap distribution, and high contrast.
[0004] The photoresist used as the spacer material is generally a negative photoresist, and has appropriate mechanical strength, good heat resistance and adhesion. Currently, most of the spacer materials on the market are acrylate photoresists, which contain many small molecules in their composition and are easy to volatilize during the process, causing equipment pollution. Therefore, it is an urgent problem for those skilled in the art to develop a negative photoresist material that meets the display panel preparation process conditions and has good mechanical properties and elastic recovery rate. Summary of the invention
[0005] The purpose of the present invention is to provide a photoresist composition having good resolution, residual film rate and elastic recovery rate. To this end, the present invention provides a negative photoresist composition and its application to solve this need in the art.
[0006] In one aspect, the present invention relates to a negative photoresist composition, comprising: a base polymer, a photoacid generator and a solvent, wherein the base polymer is composed of a first polymer obtained by polymerization of a first acrylic resin and a second polymer obtained by polymerization of a second acrylic resin;
[0007] The first acrylic resin comprises, by parts by mass, 1 to 50 parts of a first epoxy acrylate monomer (A-I), 1 to 20 parts of a first siloxane monomer (A-II), 1 to 20 parts of a first acrylate monomer (A-III) and 1 to 30 parts of a styrene monomer (A-IV);
[0008] The second acrylic resin comprises, by parts by mass, 1 to 50 parts of a second epoxy acrylate monomer (B-I), 1 to 40 parts of a second siloxane monomer (B-II) and 1 to 20 parts of a second acrylate monomer (B-III);
[0009] The styrene monomer has a structure as shown in Formula IV,
[0010]
[0011] Here, R is an alkyl or alkoxy linear substituent having 0 to 8 carbon atoms.
[0012] It is easy for those skilled in the art to know that the preparation method of the first polymer includes: a first epoxy acrylate monomer (A-Ⅰ), a first siloxane monomer (A-Ⅱ), a first silicone acrylate monomer (A-Ⅲ), a styrene monomer (A-Ⅳ), a free radical initiator and a solvent are polymerized to obtain the first polymer.
[0013] Those skilled in the art will readily appreciate that the method for preparing the second polymer includes: a second epoxy acrylate monomer (B-I), a second siloxane monomer (B-II), a second acrylate monomer (B-III), a free radical initiator and an organic solvent are polymerized to obtain the second polymer.
[0014] Exemplarily, the free radical initiator used to prepare the first polymer or the second polymer is an azo initiator, specifically 2,2'-azobis(isobutyric acid)dimethyl, 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile) and 2,2'-azobis(2,4-dimethylvaleronitrile) and methyl azobisisobutyrate, etc.; peroxide initiator: at least one of organic peroxides such as benzoyl peroxide, lauroyl peroxide, tert-butyl perbenzoate, tert-butyl peroxy-2-ethylhexanoate and persulfates such as potassium persulfate and sodium persulfate.
[0015] Optionally, during the polymerization reaction using the free radical initiator, a chain transfer agent may be added arbitrarily, specifically at least one of 2-mercaptoethanol, butyl mercaptan, n-dodecyl mercaptan, and α-methylstyrene dimer.
[0016] Illustratively, the solvent used to prepare the first polymer or the second polymer is at least one of diethylene glycol alkyl ether compounds, dipropylene glycol alkyl ether compounds, propylene glycol monoalkyl ether compounds, propylene glycol monoalkyl ether acetate compounds, N,N-dimethylamide compounds, lactate compounds, and ketone compounds.
[0017] Illustratively, the diethylene glycol alkyl ether solvents are diethylene glycol dimethyl ether, diethylene glycol diethyl ether, and diethylene glycol methyl ethyl ether; the dipropylene glycol alkyl ether solvents are dipropylene glycol dimethyl ether and dipropylene glycol diethyl ether; the propylene glycol monoalkyl ether solvents are propylene glycol monomethyl ether and propylene glycol monoethyl ether; the propylene glycol monoalkyl ether acetate solvents are propylene glycol monomethyl ether acetate and propylene glycol monoethyl ether acetate, etc.; the N,N-dimethylamide solvents are N,N-dimethylformamide and N,N-dimethylacetamide; the lactate ester solvents are methyl lactate and ethyl lactate; the ketone compounds are cyclobutanone and cyclopentanone.
[0018] Further, in the negative photoresist composition provided by the present invention, the first epoxy acrylate monomer or the second epoxy acrylate monomer is independently selected from at least one of epoxy methacrylate, glycidyl acrylate, and tetrahydrofurfuryl methacrylate;
[0019] The first siloxane monomer or the second siloxane monomer is independently selected from at least one of vinyl triisopropyl silane, vinyl pentamethyl disiloxane, 1,3-dimethyltetravinyl disiloxane, 1,3-divinyltetramethyl disiloxane, tris[dimethyl(vinyl)siloxy]phenyl silane, 1-vinyl-1,1,3,3-tetramethyl disiloxane, 1,3-bis(3-methacryloxypropyl)tetrakis(trimethylsiloxy)disiloxane, 1,3-divinyl-1,3-dimethyl-1,3-diphenyl disiloxane, methacryloxypropyl tris(trimethylsiloxy)silane, acryloxypropyl trimethoxysilane, and 3-(isomethacryloxy)propyl trimethoxysilane;
[0020] The first acrylate monomer or the second acrylate monomer is independently selected from at least one of methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, lauryl acrylate, and lauryl methacrylate.
[0021] Furthermore, in the negative photoresist composition provided by the present invention, the photoacid generator is an iodonium salt and / or a sulfonium salt.
[0022] Further, in the negative photoresist composition provided by the present invention, the iodonium salt is selected from at least one of diphenyl iodonium hexafluoroantimonate, diphenyl iodonium hexafluorophosphate, diphenyl iodonium hexafluoroarsenate, diphenyl iodonium tetrafluoroborate, ditolyl iodonium hexafluoroarsenate, and di-tert-butylphenyl iodonium hexafluorophosphate;
[0023] The sulfonium salt is selected from at least one of triphenyl sulfonium hexafluoroantimonate, triphenyl sulfonium hexafluoroarsenate, triphenyl sulfonium tetrafluoroborate, 4-methylphenyldiphenyl sulfonium hexafluorophosphate, triphenyl sulfonium hexafluorophosphate, diphenyl sulfonium, and 4-(phenylthio)phenyl sulfonium hexafluorophosphate.
[0024] Furthermore, in the negative photoresist composition provided by the present invention, the solvent is selected from at least one of dichloromethane, chloroform, tetrahydrofuran, benzene, toluene, butyrolactone, propylene glycol monoalkyl ether, propylene glycol alkyl ether acetate, cyclopentanone, butyl acetate, methyl isobutyl ketone, 2-pentanone, 4-methyl-2-pentanone, cyclohexanone, 2-heptanone, γ-butyrolactone, ethylene glycol monoethyl ether acetate, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether acetate, and N,N-dimethylformamide.
[0025] Furthermore, in the negative photoresist composition provided by the present invention, the raw materials for preparing the negative photoresist composition include, by mass percentage: 8-30% of the first acrylic resin, 2-19% of the second acrylic resin, 1-6% of the photoacid generator and 50-84% of the solvent.
[0026] Furthermore, in the negative photoresist composition provided by the present invention, the molecular weight of the first polymer is Mn=3500-6000, and PDI=1.2-2.0;
[0027] The molecular weight of the second polymer is Mn=3000-6000, and PDI=1.2-2.0.
[0028] Furthermore, in the negative photoresist composition provided by the present invention, the resolution of the negative photoresist composition is 8.0 to 8.5 microns, THK is 3.0 to 3.5 microns, the residual film rate is 88% to 91%, the viscosity is 3.0 to 3.5 cP, the outgassing is 2.0% to 3.0%, the adhesion grading evaluation is not less than +++, and the elastic recovery rate is greater than 90%.
[0029] In another aspect, the present invention relates to the use of the negative photoresist composition in spacers.
[0030] Furthermore, in the application provided by the present invention, the negative photoresist composition is used for spacers of TFT-LCD.
[0031] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages:
[0032] The negative photoresist composition prepared by the present invention can prepare spacers with different mechanical strengths by adjusting different ratios of the first acrylic resin and the second acrylic resin, and the prepared spacers have good elastic recovery rate. Since there is no small molecule monomer in the photoresist composition, there is no risk of small molecules volatilizing and polluting equipment during the photolithography process. The performance of the prepared spacer is comprehensively tested, and good supporting capacity can be maintained on the basis of ensuring good adhesion. DETAILED DESCRIPTION
[0033] The technical scheme of the present invention is described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The experimental methods and detection methods described in each embodiment are conventional methods unless otherwise specified; the reagents and materials can be purchased on the market unless otherwise specified. The % in the following embodiments, unless otherwise specified, are all mass percentages. The ratios in the following embodiments, unless otherwise specified, are all mass ratios.
[0034] Example 1
[0035] This embodiment provides a method for synthesizing acrylic resin A.
[0036] Under nitrogen protection, 200.0 g of glycidyl methacrylate, 20.0 g of 1-vinyl-1,1,3,3-tetramethyldisiloxane, 45.0 g of methyl methacrylate, 120.0 g of styrene, 10.0 g of azobisisoheptanenitrile, and 5.0 g of α-methylstyrene dimer were added to a 1L three-necked flask, and the temperature was raised to 80°C under stirring, and the temperature was lowered to room temperature after reacting for 6 hours to obtain acrylic resin solution A-1. Mn = 4500, PDI = 1.7.
[0037] Example 2
[0038] This embodiment provides a method for synthesizing acrylic resin A.
[0039] Under nitrogen protection, 155.0 g of glycidyl methacrylate, 45.0 g of 1-vinyl-1,1,3,3-tetramethyldisiloxane, 80.0 g of methyl methacrylate, 150.0 g of styrene, 10.0 g of azobisisoheptanenitrile, and 5.0 g of α-methylstyrene dimer were added to a 1L three-necked flask, and the temperature was raised to 80°C under stirring, and the temperature was lowered to room temperature after reacting for 6 hours to obtain acrylic resin solution A-2. Mn = 5500, PDI = 1.8.
[0040] Example 3
[0041] This embodiment provides a method for synthesizing acrylic resin A.
[0042] Under nitrogen protection, 215 g of tetrahydrofurfuryl methacrylate, 20.0 g of methacryloyloxypropyl tris(trimethylsiloxy)silane, 55.0 g of butyl methacrylate, 100.0 g of α-methylstyrene, 10.0 g of azobisisoheptanenitrile, and 5.0 g of α-methylstyrene dimer were added to a 1L three-necked flask, and the temperature was raised to 80°C under stirring, and the temperature was lowered to room temperature after reacting for 8 hours to obtain acrylic resin solution A-3. Mn = 6000, PDI = 1.8.
[0043] Example 4
[0044] This embodiment provides a method for synthesizing acrylic resin A.
[0045] Under nitrogen protection, 175.0 g of 3,4-epoxycyclohexylmethyl methacrylate, 25.0 g of acryloxypropyl methoxysilane, 60.0 g of ethyl methacrylate, 135.0 g of α-methylstyrene, 10.0 g of azobisisoheptanenitrile, and 5.0 g of α-methylstyrene dimer were added to a 1L three-necked flask, and the temperature was raised to 80°C under stirring, and the temperature was lowered to room temperature after reacting for 8 hours to obtain acrylic resin solution A-4. Mn = 5000, PDI = 1.8.
[0046] Example 5
[0047] This embodiment provides a method for synthesizing acrylic resin B.
[0048] Under nitrogen protection, 220.0 g of tetrahydrofurfuryl methacrylate, 110.0 g of 1-vinyl-1,1,3,3-tetramethyldisiloxane, 35.0 g of methyl acrylate, 10.0 g of azobisisoheptanenitrile, and 5.0 g of α-methylstyrene dimer were added to a 1L three-necked flask, and the temperature was raised to 80°C under stirring, and the temperature was lowered to room temperature after reacting for 6 hours to obtain acrylic resin solution B-1. Mn = 4800, PDI = 1.7.
[0049] Example 6
[0050] This embodiment provides a method for synthesizing acrylic resin B.
[0051] Under nitrogen protection, 200.0 g of glycidyl methacrylate, 160.0 g of 1-vinyl-1,1,3,3-tetramethyldisiloxane, 25.0 g of ethyl acrylate, 10.0 g of azobisisoheptanenitrile, and 5.0 g of α-methylstyrene dimer were added to a 1L three-necked flask, and the temperature was raised to 80°C under stirring, and the temperature was lowered to room temperature after reacting for 6 hours to obtain acrylic resin solution B-2. Mn = 5000, PDI = 1.7.
[0052] Example 7
[0053] This embodiment provides a method for synthesizing acrylic resin B.
[0054] Under nitrogen protection, 200.0 g of tetrahydrofurfuryl methacrylate, 120.0 g of methacryloyloxypropyl tris(trimethylsiloxy)silane, 65.0 g of butyl acrylate, 10.0 g of azobisisoheptanenitrile, and 5.0 g of α-methylstyrene dimer were added to a 1L three-necked flask, and the temperature was raised to 80°C under stirring, and the temperature was lowered to room temperature after reacting for 8 hours to obtain acrylic resin solution B-3. Mn = 5500, PDI = 1.8.
[0055] Example 8
[0056] This embodiment provides a method for synthesizing acrylic resin B.
[0057] Under nitrogen protection, 200.0 g of glycidyl acrylate, 120.0 g of acryloxypropyl methoxysilane, 65.0 g of tert-butyl methacrylate, 10.0 g of azobisisoheptanenitrile, and 5.0 g of α-methylstyrene dimer were added to a 1L three-necked flask, and the temperature was raised to 80°C under stirring. After reacting for 8 hours, the temperature was lowered to room temperature to obtain acrylic resin solution B-4. Mn = 5200, PDI = 1.7.
[0058] Example 9
[0059] This embodiment provides a method for preparing a negative photoresist composition R.
[0060] Under nitrogen protection, 20 g of acrylic resin A-1, 10 g of acrylic resin B-1, 5 g of photoacid generator diphenylsulfonium salt, and 65 g of solvent cyclopentanone were added into a 250 mL three-necked flask and dissolved to obtain a negative photoresist composition R1.
[0061] Examples 10 to 20, Comparative Examples 1 to 8
[0062] The preparation methods of Examples 10 to 20 and Comparative Examples 1 to 8 are the same as those of Example 9, and negative photoresist resin compositions R2 to R20 are prepared. The difference lies in the different types and qualities of acrylic resins.
[0063] Table 1: Photoresist composition formula
[0064]
[0065] Embodiment 21
[0066] This embodiment provides a method for preparing a photoresist spacer S.
[0067] The photoresist composition R1 was spin-coated on a clean glass sheet at a speed of 300 rpm for 15 seconds, and pre-baked at 90°C for 2 minutes. After the pre-baking, mask exposure was performed for 10 seconds, and then dried and cured at 120°C. 2.38% tetramethylammonium hydroxide solution (TMAH) was used as the developer, and the development was performed for 60 seconds to obtain a photoresist spacer S1 with a height of 3 microns.
[0068] Embodiments 22 to 32
[0069] The preparation method of Examples 22 to 32 is the same as that of Example 21, and photoresist spacers S2 to S12 are prepared. The difference is that negative photoresist compositions R2 to R12 are selected.
[0070] Embodiment 33
[0071] This embodiment provides a testing method for a negative photoresist composition R and a photoresist spacer S.
[0072] (1) GPC instrument: Agilent 1260; chromatographic column: Agilent Plege 3μm MIXED-D (300mm*7.5mm)*2; mobile phase: THF; flow rate: 1.0mL / min; detector: RID detector; acquisition time: 30min; workstation: AgilentGPC;
[0073] (2) Photolithography instrument: SUSS-MJB4; wavelength: i\g mixed line; exposure: 30~70mJ;
[0074] (3) Film coating instrument: MycroWS-650MZ-23NPPB; rotation speed: 300~1000rpm;
[0075] (4) Viscosity instrument: Anton Paar VISCOQC-100; measurement temperature: 25°C;
[0076] (5) Adhesion instrument: cross-cut tester (BYK5123, number of teeth: 11, spacing between teeth: 1 mm), 3M610 tape is used as the adhesive tape; test method and evaluation standard: refer to GB / T9286-2021;
[0077] (6) Film thickness instrument: step profiler; model: Bruker Dektak150;
[0078] (7) Residual film rate: the ratio of the film thickness before baking to the film thickness of the coating.
[0079] (8) Outgassing instrument: GC-MS; test conditions: 40℃*2min-230℃ (10℃ / min)-230℃*180min.
[0080] Comparative Example 9
[0081] The purchased photoresist composition (main resin acrylate) was spin-coated on a clean glass sheet at a rotation speed of 500 rpm for 15 seconds, and pre-baked at 90°C for 2 minutes. After the pre-baking, mask exposure was carried out for 10 seconds, and then dried and cured at 120°C. 2.38% tetramethylammonium hydroxide solution (TMAH) was used as the developer, and the development was carried out for 60 seconds to obtain a photoresist spacer S21 with a height of 3 microns.
[0082] Comparative Examples 10-17
[0083] The preparation methods of control examples 10 to 17 are the same as those of example 21, and photoresist spacers S21 to S28 are prepared. The difference is that the negative photoresist compositions R13 to R20 are selected.
[0084] Table 2: Performance test results of photoresist spacers prepared in Examples 21 to 32 and Comparative Examples 9 to 17
[0085]
[0086] Note: Adhesion grading evaluation standard: ++++ - the edges are neat and smooth, without any peeling; +++ - the total peeling area of the cross-cut area does not exceed 5%; ++ - the total peeling area of the cross-cut area is greater than 5%, but not more than 15%; + - the total peeling area of the cross-cut area is greater than 15%, but not more than 35%.
[0087] As can be seen from Table 2, the CD values of Examples 21 to 32 are relatively uniform, consistent with the 8-micron precision of the mask specification, and have good adhesion and elastic recovery rate, indicating that the photoresist spacer prepared by the present invention meets the requirements of the process conditions. Comparative Examples 9-13 use a single photoresist composition configured with acrylic resin A to prepare photoresist spacers, and the adhesion and elastic recovery rate are significantly reduced. Comparative Examples 14-17 use a single photoresist composition configured with acrylic resin B to prepare photoresist spacers, and the resolution becomes worse and the outgassing becomes larger.
[0088] As described above, the basic principle, main features and advantages of the present invention are well described. The above embodiments and descriptions are only descriptions of the preferred implementation modes of the present invention, and the present invention is not limited by the above embodiments. Without departing from the spirit and scope of the present invention, various changes and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the protection scope determined by the present invention.
Claims
1. A negative photoresist composition comprising: A base polymer, a photoacid generator and a solvent, wherein the base polymer is composed of a first polymer obtained by polymerization of a first acrylic resin and a second polymer obtained by polymerization of a second acrylic resin; In parts by mass, the first acrylic resin includes 1 to 50 parts of a first epoxy acrylate monomer, 1 to 20 parts of a first siloxane monomer, 1 to 20 parts of a first acrylate monomer, and 1 to 30 parts of a styrene monomer; The second acrylic resin includes, by weight, 1 to 50 parts of a second epoxy acrylate monomer, 1 to 40 parts of a second siloxane monomer, and 1 to 20 parts of a second acrylate monomer; The styrene monomer has a structure as shown in Formula IV, Wherein, R is an alkyl or alkoxy linear substituent having 0 to 8 carbon atoms; The first siloxane monomer or the second siloxane monomer is independently selected from at least one of vinyl triisopropyl silane, vinyl pentamethyl disiloxane, 1,3-dimethyltetravinyl disiloxane, 1,3-divinyltetramethyl disiloxane, tris[dimethyl(vinyl)siloxy]phenyl silane, 1-vinyl-1,1,3,3-tetramethyl disiloxane, 1,3-bis(3-methacryloxypropyl)tetrakis(trimethylsiloxy)disiloxane, 1,3-divinyl-1,3-dimethyl-1,3-diphenyl disiloxane, methacryloxypropyl tris(trimethylsiloxy)silane, acryloxypropyl trimethoxysilane, and 3-(isomethacryloxy)propyl trimethoxysilane.
2. The negative photoresist composition according to claim 1, characterized in that The first epoxy acrylate monomer or the second epoxy acrylate monomer is independently selected from at least one of epoxy methacrylate, glycidyl acrylate, and tetrahydrofurfuryl methacrylate; The first acrylate monomer or the second acrylate monomer is independently selected from at least one of methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, lauryl acrylate, and lauryl methacrylate.
3. The negative photoresist composition according to claim 1, characterized in that: The photoacid generator is an iodonium salt and / or a sulfonium salt.
4. The negative photoresist composition according to claim 3, characterized in that: The iodonium salt is selected from at least one of diphenyl iodonium hexafluoroantimonate, diphenyl iodonium hexafluorophosphate, diphenyl iodonium hexafluoroarsenate, diphenyl iodonium tetrafluoroborate, ditolyl iodonium hexafluoroarsenate, and di-tert-butylphenyl iodonium hexafluorophosphate; The sulfonium salt is selected from at least one of triphenyl sulfonium hexafluoroantimonate, triphenyl sulfonium hexafluoroarsenate, triphenyl sulfonium tetrafluoroborate, 4-methylphenyldiphenyl sulfonium hexafluorophosphate, triphenyl sulfonium hexafluorophosphate, diphenyl sulfonium, and 4-(phenylthio)phenyl sulfonium hexafluorophosphate.
5. The negative photoresist composition according to claim 1, characterized in that: The solvent is selected from at least one of dichloromethane, chloroform, tetrahydrofuran, benzene, toluene, butyrolactone, propylene glycol monoalkyl ether, propylene glycol alkyl ether acetate, cyclopentanone, butyl acetate, methyl isobutyl ketone, 2-pentanone, 4-methyl-2-pentanone, cyclohexanone, 2-heptanone, γ-butyrolactone, ethylene glycol monoethyl ether acetate, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether acetate, and N,N-dimethylformamide.
6. The negative photoresist composition according to any one of claims 1 to 5, characterized in that: In terms of mass percentage, the raw materials for preparing the negative photoresist composition include: 8-30% of the first acrylic resin, 2-19% of the second acrylic resin, 1-6% of the photoacid generator and 50-84% of the solvent.
7. The negative photoresist composition according to claim 1, characterized in that: The molecular weight of the first polymer is Mn=3500-6000, and PDI=1.2-2.0; The molecular weight of the second polymer is Mn=3000-6000, and PDI=1.2-2.
0.
8. The negative photoresist composition according to claim 1, characterized in that: The negative photoresist composition has a resolution of 8.0 to 8.5 microns, a THK of 3.0 to 3.5 microns, a residual film rate of 88% to 91%, a viscosity of 3.0 to 3.5 cP, an outgassing of 2.0% to 3.0%, an adhesion grading evaluation of not less than +++, and an elastic recovery rate of more than 90%.
9. Use of the negative photoresist composition according to any one of claims 1 to 8 in spacers.
10. The use according to claim 9, characterized in that: The negative photoresist composition is used for spacers of TFT-LCD.
Citation Information
Patent Citations
Chemical amplitude-increasing type silicon-containing I-line ultraviolet negative photoresist and forming resin thereof
CN102050908A
Radiation-sensitive resin composition, method for forming spacer and interlayer insulating film for display device, and display device
CN104950575A